A Spanish Version of the Achievement Task Value Scale for University Students: Internal, Convergent, and Criterion Validity and Reliability in Argentinian Students - Sánchez Rosas, Javier; Lou, Yu-Chiung; Lin, Hsiao-Fang; Larroza, Silvana (Pensando Psicología, 2017)
Objective: An Achievement Task Value Scale Spanish Language Adjusted Version, assessing task value items corresponding to importance, utility, interest and cost, was evaluated regarding its psychometric properties, in a sample of Argentine students. Method: In order to assess internal structure, exploratory and confirmatory strategies have been used. Besides, scale convergence was assessed by relating them with a one-dimensional task value scale. Evidences of criterion validity were supported by relating scales with enjoyment, achievement goals, and attention. Finally, internal consistency was estimated using Cronbach’s Alpha and Omega coefficients. Conclusions: Results allow to state that this version of the instrument makes it possible to assess, in a reliable and valid way, three components of task value: utility, interest, and cost.